An exploratory study of service productivity index for service industry evaluation. (11th December 2012) - Indrianti, Nur
This paper presents an exploratory study of service productivity index (SPI). Given the weakness of the previous service productivity measurements, this paper presents an improvement in measuring service productivity. With regard to the basic principal of productivity, it is proposed to measure service productivity as the ratio between effectiveness and efficiency. The effectiveness is measured by customer satisfaction, while the efficiency is measured by the ratio between cost of producing the service and revenue. We examined the use of the proposed index using a case study of internet cafes in Indonesia. The result of the study proves that both efficiency and effectiveness in utilising resources are important and affect service productivity. Practically, the proposed SPI can be implemented in any service sector. Moreover, it can be used for evaluating the performance of firms in the same cluster with the same attributes to measure.